Distribution of Tissue Factor Pathway Inhibitor in Normal and Malignant Human Tissues - Werling, Robert W; Zacharski, Leo R; Kisiel, Walter; Bajaj, S Paul; Memoli, Vincent A; Rousseau, Sandra M (Thrombosis and Haemostasis, 1993)
Specific antibodies to tissue factor pathway inhibitor (TFPI) were used in immunohistochemical procedures to determine the distribution of TFPI in normal and neoplastic human tissues. TFPI was restricted to megakaryocytes and the endothelium of the microvasculature in normal and abnormal tissues, but was not found in the endothelium of larger vessels or in hepatocytes. TFPI was also detected in macrophages in the villi of term placenta. Tumor-associated macrophages in several types of malignancy that we have shown previously to express a complete tissue factor-initiated pathway of coagulation and thrombin generation also manifested TFPI. By contrast, malignant cells in small cell carcinoma of the lung, renal cell carcinoma, and malignant melanoma that we have shown previously to express coagulation factors together with tumor cell-associated fibrin formation failed to stain for TFPI. We postulate that TFPI may be lacking from the latter malignancies because of the absence of the appropriately configured tissue factor – factor VII a – factor Xa complex required for TFPI binding.